Molecular Mechanisms of Water Transport Across Biological Membranes - Zeuthen, Thomas; Stein, Wilfred D. (International review of cytology ;, 2002)
International Review of Cytology presents current advances and comprehensive reviews in cell biology--both plant and animal. Authored by some of the foremost scientists in the field, each volume provides up-to-date information and directions for future research. This volume looks at water movements from a wide range of levels. It examines how water interacts with the major components of the cell, including proteins and lipids. It discusses how water moves across cell membranes by diffusion, how it is chanelled across these membranes or, in certain cases, pumped across, and how water movements are controlled. This book demonstrates how water and ion movements are closely linked in order to provide a better understanding of their behavior. *Essential Physical chemistry of water at biological interfaces *Up-to-date reviews of water behavior in cells *Water in integrated systems *Current information on water channels across membranes.